Assessment and indicators of hallux limitus related with quality of life and foot health in school children - Cuevas-Martínez, Claudia; Becerro-de-Bengoa-Vallejo, Ricardo; Losa-Iglesias, Marta Elena; Navarro-Flores, Emmanuel; Pérez-Palma, Laura; Martiniano, João; López-López, Daniel; Casado-Hernández, Israel; Gómez-Salgado, Juan (Frontiers in Pediatrics, 2023)
Background:Functional Hallux Limitus (FHL) is a dynamic foot dysfunction characterized by a limitation of hallux dorsiflexion when the first metatarsal head is under load. FHL plays a role in the development of osteoarthrosis in the first metatarsophalangeal joint (IMTPJ). Forefoot disorders can significantly impact an individual's quality of life, leading to dysfunction and pain. The aim of this project was to evaluate the quality of life of school-aged individuals with and without FHL using the Foot Health Status Questionnaire(FHSQ).Methods: A case-control study was conducted to evaluate the outcomes in paediatric age. A total sample of 116 children between 6-12 years old was used to conduct this research. The sample was divided into two groups: (i) the healthy group (n=58) and the FHL group (n=58).The FHSQ was completed and the FHL test was performed in a seated position to classify the patients into the selected group. Results:Non-significant changes were observed when the mean values of the FHSQ domains were compared between the groups with and without FHL, except for the "general foot health" domain (p=0,024) associated with the specific foot health section (section 1) of the Questionnaire. For the domains linked with the general well-being section (section 2), there was not a statistically difference in the mean of the scores obtained between the two school-aged groups with and without FHL, being slightly lower in the group with the presence of FHL for the overall health and physical function domains. Both the healthy and case groups obtained and identical range of scores (10-100) for the "foot pain" domain. Nevertheless, the mean of the score was lower for the participants with FHL.Conclusions:The perception of the quality of general foot health 3 was poorer in the school-aged group with FHL. Variables such as foot pain and footwear are likely contributors influencing the perception of foot health quality. The school-aged population with FHL faces a decline in the quality of foot life. Ensuring adequate foot control in children and implementing future foot programs for this population are imperative for enhancing school children's perception of foot health and managing the development of pain and footwear-related issues.